Use of stereolithographic drilling and cutting guides in bilateral mandibular distraction - Seeberger, Robin; Davids, Rolf; Kater, Wolfgang; Thiele, Oliver C. (The journal of craniofacial surgery, 2011)
Mandibular distraction osteogenesis is used in the treatment of patients with syndromic and nonsyndromic class II mandibular hypoplasia. The three-dimensional distraction of the mandible is extremely complex. Past experience with mandibular distraction has demonstrated the indispensability of solid presurgical planning to achieve predictable results. We report a method for a virtual three-dimensional planning of the bilateral mandibular distraction with intraoperative transfer by stereolithographic guides. Five patients (mean age, 22.8 years) with bilateral mandibular hypoplasia were examined with preoperative and postoperative computed tomographic scans. The direction and dimension of the distraction were planned on the three-dimensional computed tomographic scans. Tooth- and bone-borne stereolithographic guides for transferring the planning were then applied intraoperatively. It was feasible to transfer and perform the surgery as planned by the use of the stereolithographic drilling and cutting guides. The mean distraction width was 11.33 (SD, 8.32) mm. The mean difference of the distraction width between the planning and the achieved final mandibular position was 1.80 (SD, 0.43) mm. The intercondyle distance decreased by 3.28 (SD, 1.01) mm. A parallel distraction within the planned vectors was achieved. Mandibular distraction osteogenesis in the treatment of severe mandibular hypoplasia needs careful presurgical planning. Parallel distraction and fast placement of the distractors are provided by the planning. The method provides a useful tool for both planning and intraoperative transfer of the virtually preplanned distraction vectors.
Gesehen am 31.10.2022